Acyl-CoA dehydrogenase activity in pea cotyledon tissue during germination and initial growth. (December 2000) - Masterson, C.; Blackburn, A.; Wood, C.
Abstract : Acyl-CoA dehydrogenase activity has been measured in homogenates of post-imbibition to 14-day-old hydroponically grown pea seeds at daily intervals, using C4, C12 and C16 acyl-CoA substrates. The activity peaks of the different chain-length acyl-CoA dehydrogenases did not transpose at all points and the ratios of the chain-length activities were not constant. It therefore has to be concluded that more than one dehydrogenase is present in pea mitochondria. There was a post-imbibition initial surge of activity with short- and mid-chain-length substrates. The C16- handling enzyme first peaked at 3–4 days, which coincided with the onset of plumule unfurling and greening. Further peaks were observed with all three substrates, coinciding with secondary root formation and leaf enlargement and later with cotyledon degeneration. Overall activity showed that the long-chain acyl-CoA dehydrogenase was much more active than the short-chain acyl-CoA dehydrogenase.